2023
DOI: 10.1021/acs.est.2c08463
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure of Zebrafish (Danio rerio) to the Next-Generation Perfluoroalkyl Substance, Perfluoroethylcyclohexanesulfonate, Shows Similar Effects as Legacy Substances

Abstract: Perfluoroethylcyclohexanesulfonate (PFECHS) is an emerging perfluoroalkyl substance (PFAS) that has been considered a potential replacement for perfluorooctanesulfonic acid (PFOS). However, there is little information characterizing the toxic potency of PFECHS to zebrafish embryos and its potential for effects in aquatic environments. This study assessed toxic potency of PFECHS in vivo during both acute (96-hour postfertilization) and chronic (21-day posthatch) exposures and tested concentrations of PFECHS fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Interestingly, it has been shown that PFOS can directly bind to apoA‐I in fish (Honda et al, 2014), potentially contributing to the accumulation of PFOS; this may represent a PPAR‐independent means by which PFOS interferes with cholesterol metabolism and homeostasis. Finally, it is known that apoA‐I and CETP are expressed in yolk of zebrafish (Fraher et al, 2016), and can, accordingly, play a role in the development of early life stages of fish—because the transport of lipids from the yolk to the embryo is vital to fish development (Mahoney et al, 2023)—and observed alterations in CEs may thus additionally suggest a mechanism for the observed embryotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been shown that PFOS can directly bind to apoA‐I in fish (Honda et al, 2014), potentially contributing to the accumulation of PFOS; this may represent a PPAR‐independent means by which PFOS interferes with cholesterol metabolism and homeostasis. Finally, it is known that apoA‐I and CETP are expressed in yolk of zebrafish (Fraher et al, 2016), and can, accordingly, play a role in the development of early life stages of fish—because the transport of lipids from the yolk to the embryo is vital to fish development (Mahoney et al, 2023)—and observed alterations in CEs may thus additionally suggest a mechanism for the observed embryotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Limited toxicological data are available for replacement PFASs especially for apex predators and humans, but studies on rats, mice, and fish have started to demonstrate that a number of compounds have the potential to cause toxic effects. ,,, Further research is needed on toxicity as well as their potential to bioaccumulate and biomagnify, and thus, the risk to apex predators and humans. As chemical companies continue to innovate, industry confidentiality and the time needed to develop analytical methods mean research and regulatory risk assessment inevitably lag behind production. , One of the biggest challenges in targeted PFAS analysis is the lack of reference standards, and this risks regrettable substitutions. , Increased collaboration between industry, research, and regulation is urgently needed.…”
Section: Resultsmentioning
confidence: 99%
“…PFECHS was reported to suppress the growth of microalgae (marine Chlorella sp.) and cause endocrine disruption in zooplankton ( Daphnia magna ). , Further, PFECHS (concentrations of 0.5–2000 μg/L) exposure can boost the abundance of transcripts of some key genes (e.g., cytochrome P450 1A1) in zebrafish . In addition, a significant downregulation of glutathione- S -transferase was observed in the liver cells (RTL-W1) of the rainbow trout ( Oncorhynchus mykiss ) after exposure to PFECHS at 400 ng/L .…”
Section: Introductionmentioning
confidence: 99%